Precise Management of Chiari Malformation with Type I - Guo, Fuyou; Turgut, Mehmet (Frontiers in Surgery, 2022)
Diagnosis of Chirai malformation type I (CM-I) is based on magnetic resonance imaging of the brain or cervical spinal cord. The main goal of surgery is to relieve the blockage to the free pulsatile flow of cerebrospinal fluid beyond the foramen magnum and to stop the progression of a syringomyelia. Despite recent advances in imaging and surgery, even today, there is no consensus on optimal management of CM-I. Ongoing focus is devoted to a better consideration of the pathophysiology of CM-I and the development of more effective medical and surgical treatments. It is hoped that proposed algorithm helps the neurosurgeon to provide a precise management for patients with CM-I in advance.